Wind turbine modelling and simulation using Matlab/SIMULINK - Chi Hung, Chong; Andrew Ragai Henry, Rigit; Ali, I. (IOP Publishing Ltd, 2021)
Malaysia is aiming to reduce the dependency on oil and gas by increasing the utilization of renewable energy. One of the promising renewable energy available is wind energy. Malaysia is located near the equator which is situated in a low wind speed region with an annual mean wind speed of 1.2-4.1 m/s. However, Malaysia also experiences two different monsoon seasons which is the southwest monsoon and the northeast monsoon. Wind speed during the southwest monsoon season can reach 7 m/s while the wind speed during the northeast monsoon can exceed 15 m/s. Limited researches and studies had been done to investigate the potentiality of wind energy in Sarawak, Malaysia. In this paper, modelling and simulation of different wind energy conversion system (WESC) using different generators operating under the same parameters will be carried out using MATLAB/SIMULINK to investigate the efficiency of the generators. PMSG has shown to be more efficient over SCIG and DFIG for lower wind speed although all of them eventually reaches the similar efficiency. Efficiency of SCIG, DFIG and PMSG for rated wind speed are 66.25%, 69.38% and 71.88% respectively.